Preparation and characterization of poly(lactic-co-glycolic acid) nanoparticles containing TGF-beta 1 and evaluation of in vitro wound healing effect - SEZER, ALİ DEMİR; ŞAHBAZ, SEVİNÇ; UĞURLU, TİMUÇİN (MARMARA UNIV, 2020)
( )Wound healing involves many complex mechanisms, and many growth factors are effective in this process. Growth factors are biologically active polypeptides. They perform activities such as cell growth, differentiation, proliferation and migration with molecular cascades by binding to specific receptors. Transforming growth factor stimulates (TGF-beta) different cell types in the wound healing process. Poly(lactic-co-glycolic acid) (PLGA) degradation produces lactate that expedites angiogenesis, activates pro-collagen factors. Therewith, we hypothesized to combine the therapeutic effect of the TGF-beta 1with the positive effect of the drug delivery system including PLGA nanoparticles (TGF beta-PLGA NP). The burst effect decreases as the polymer concentration increases in PLGA nanoparticles. The inhibitory effect of TGF-beta 1 on keratinocytes was reduced by the improved nanoparticle formulations. It showed a proliferative effect of up to 92.5 per cent on fibroblast cells involved in wound healing. Although TGF-beta 1 has an inhibitory effect on keratinocytes, it induces migration both NIH-3T3 and HaCaT cell lines in the scratch assay.
Keywords: Transforming growth factor; PLGA; nanoparticle; wound healing; DRUG-DELIVERY; PLGA NANOPARTICLES; CONTROLLED-RELEASE; GROWTH; SYSTEMS; MICROSPHERES; FORMULATION